Attenuation of leakiness in doxycycline-inducible expression via incorporation of 3′ AU-rich mRNA destabilizing elements. (August 2008) - Pham, Duyen H.; Moretti, Paul A.B.; Goodall, Gregory J.; Pitson, Stuart M.
Tetracycline-regulated expression systems have been widely used for inducible protein expression in cultured mammalian cells. With these systems, however, leakiness in expression of the target gene in the absence of the inducing agent is a frequent problem. Here we describe a novel approach to overcome this problem that involves the incorporation of AU-rich mRNA destabilizing elements (AREs) into the 3′ untranslated regions of the tetracycline-inducible constructs. Using the inducible expression of sphingosine kinase 1 and 2 in HEK293 cells as model systems, we found this ARE approach to be remarkably successful in ablating expression of these proteins in the absence of doxycycline through decreasing stability of their mRNAs. We show that this undemanding and flexible process results in a substantial decrease in the leakiness of the tetracycline-inducible expression system while maintaining a high level of target protein expression following induction.